Π‐Extended Polyaromatic Hydrocarbons by Sustainable Alkyne Annulations through Double C−H/N−H Activation. Issue 71 (9th December 2019) - Gońka, Elżbieta; Yang, Long; Steinbock, Ralf; Pesciaioli, Fabio; Kuniyil, Rositha; Ackermann, Lutz
Abstract: The widespread applications of substituted diketopyrrolopyrroles (DPPs) call for the development of efficient methods for their modular assembly. Herein, we present a π‐expansion strategy for polyaromatic hydrocarbons (PAHs) by C−H activation in a sustainable fashion. Thus, twofold C−H/N‐H activations were accomplished by versatile ruthenium(II)carboxylate catalysis, providing step‐economical access to diversely decorated fluorogenic DPPs that was merged with late‐stage palladium‐catalyzed C−H arylation on the thus‐assembled DPP motif. Abstract : PAHs : Double C−H/N−H activation by ruthenium(II) catalysis enabled the assembly of π‐expanded diketopyrrolopyrroles with unique spectroscopic features (see scheme).